Shape memory alloy/glass fiber woven composite for soft morphing winglets of unmanned aerial vehicles. (15th April 2016) - Han, Min-Woo; Rodrigue, Hugo; Kim, Hyung-Il; Song, Sung-Hyuk; Ahn, Sung-Hoon
Abstract: Morphing technology is inspired by biological motion for implementation in missions in a variety of areas without shape-change device. This study investigates the aerodynamic performance of a self-contained morphing winglet for an unmanned aerial vehicle (UAV) that mimics the wing-tip feathers of gliding birds. A smart soft composite (SSC), formed of shape memory alloy (SMA) wires and glass fibers within a soft polymeric matrix, was used to fabricate morphing winglets. Experiments were conducted with various diameters and numbers of embedded SMA wires, and numbers of the glass-fiber fabric lamina, which were compared with an analytical model. Morphing winglets were implemented at both wing tips of a WASP 4/7-scale UAV, and the aerodynamic characteristics were investigated using a wind tunnel testing with various attack angles. As results, when the morphing winglet was actuated, the lift-to-drag ratio increased by 5.8% compared with the flat wing geometry for attack angle greater than 5°.